Seagrass Community Structure in Mangket Beach Water, Kema District, North Minahasa Regency - Wakkary, Paramitha G.; Mandagi, Stephanus V.; Kondoy, Khristin I. F.; Kepel, Rene Ch.; Menajang, Febry S. I.; Rangan, Jety (Jurnal Ilmiah Platax, 2024)
The purpose of this study was to determine the types of seagrasses, density, relative density, frequency, diversity index, dominance index, and environmental factors in Mangket coastal waters. This research method is the quadratic and line transect. This research was conducted in the waters of Mangket Beach, Kema District, North Minahasa Regency on November 27, 2022. There were 3 species of seagrass found in Mangket Beach waters, namely, Cymodocea rotundata, Cymodocea serrullata, and Enhalus acoroides. The number of seagrass species stands at the study site ranged from 105-814 individuals, species density (4.38-33.92 individuals/m2), relative density (6.54-50.72%), frequency of presence (1.67-4 .00), relative frequency (17.24-41.38%), diversity index H'= (0.38) and dominance index (0.004-0.26). The environmental conditions in the waters are temperature 29.5°C, salinity 32‰, and sandy and sandy mud substrates. Keywords: Mangket Beach, seagrasses, community structures. Abstrak Tujuan penelitian ini adalah untuk mengetahui Struktur Komunitas Lamun meliputi jenis-jenis lamun, kepadatan, kepadatan relatif, frekuensi, frekuensi relatif, indeks keanekaragaman, indeks dominasi dan faktor lingkungan perairan pantai Mangket. Metode penelitian ini adalah kuadrat dan line transek. Penelitian ini dilaksanakan di perairan Pantai Mangket Kecamatan Kema Kabupaten Minahasa Utara pada tanggal 27 November 2022. Spesies lamun yang ditemukan di perairan Pantai Mangket berjumlah 3 yaitu, Cymodocea rotundata, Cymodocea serrullata dan Enhalus acoroides. Jumlah tegakan spesies lamun di lokasi penelitian berkisar dari 105-814 individu, kepadatan spesies (4,38-33,92 individu/m2), kepadatan relatif (6,54-50,72%), frekuensi kehadiran (1,67-4,00), frekuensi relatif (17,24-41,38%), indeks keanekaragaman H’= (0,38) dan indeks dominasi (0,004-0,26). Kondisi lingkungan di perairan yakni suhu 29,5°C, salinitas 32‰, substrat lumpur berpasir dan berpasir. Kata Kunci: Pantai Mangket, lamun, struktur komunitas.